The economic consequences of being left-handed: Some sinister results - Kevin Denny; Vincent O'Sullivan (University College Dublin, Department of Economics, 2004)
This paper provides the first estimates of the effects of handedness on hourly earnings using data on a sample of 33 year olds in the United Kingdom. Augmenting a conventional earnings equation with indicators of left handedness shows there is a well determined positive effect on male earnings with non-manual workers enjoying a slightly larger premium once we allow for non random selection into occupation. This is not consistent with the view that left-handers in general are in some sense handicapped either being innately or through experiencing a world geared towards right-handers. It is consistent with the popular notion of left-handers having particular talents such as enhanced creativity. The results for females however reveal the opposite, left-handed females are paid significantly less.
hdl:10197/945
Keywords: 330; earnings; brain; left-handed